2020
DOI: 10.1186/s12880-020-00475-2
|View full text |Cite
|
Sign up to set email alerts
|

Using CT texture analysis to differentiate between peripheral lung cancer and pulmonary inflammatory pseudotumor

Abstract: Background: This study is to distinguish peripheral lung cancer and pulmonary inflammatory pseudotumor using CT-radiomics features extracted from PET/CT images. Methods: In this study, the standard 18F-fluorodeoxyglucose positron emission tomography/ computed tomography (18 F-FDG PET/CT) images of 21 patients with pulmonary inflammatory pseudotumor (PIPT) and 21 patients with peripheral lung cancer were retrospectively collected. The dataset was used to extract CT-radiomics features from regions of interest (R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
1
29
1
Order By: Relevance
“…Different from subjective image feature analysis, CT texture analysis can extract a variety of feature parameters from the image texture that cannot be distinguished by the naked eye and quantitatively analyse the heterogeneity of lesion tissue structure, and tumour heterogeneity is one of the important features that distinguishes malignant tumours from normal tissues or benign lesions [ 18 ]. Studies have shown that texture analysis based on CT images has good application prospects for the diagnosis of benign and malignant pulmonary lesions, pathological classification and staging of lung cancer [ 19 21 ]. The ERT is an integrated machine learning algorithm, and its base estimator is a decision tree.…”
Section: Discussionmentioning
confidence: 99%
“…Different from subjective image feature analysis, CT texture analysis can extract a variety of feature parameters from the image texture that cannot be distinguished by the naked eye and quantitatively analyse the heterogeneity of lesion tissue structure, and tumour heterogeneity is one of the important features that distinguishes malignant tumours from normal tissues or benign lesions [ 18 ]. Studies have shown that texture analysis based on CT images has good application prospects for the diagnosis of benign and malignant pulmonary lesions, pathological classification and staging of lung cancer [ 19 21 ]. The ERT is an integrated machine learning algorithm, and its base estimator is a decision tree.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning contrast media application, texture features might slightly differ between native CT scans and contrast-enhanced CT scans. A recent study employed texture analysis in native CT scans derived from PET-CT to discriminate peripheral lung cancer and inflammatory pseudotumor with promising results [ 36 ]. Moreover, reconstruction algorithms of the CT images seem to influence radiomics features [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach of relying on extraction of features from a primary image is typical of radiomics, where image transformation techniques are used for advanced analysis, which can potentially reveal additional disease features and facilitate classification of neoplastic lesions. Therefore, in the context of radiomics, the PCUL-FDG method can be treated as this type of analysis, using the characteristics of shapes to assess the character of pulmonary nodules [ 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%